Prospects for implementation of digital technologies in logistics (Journal of Economic Research & Business Administration, 2018)
Over the past decades, the world is rapidly moving towards a new type of economy, where digitaltechnologies are becoming the main tool for its formation. In modern conditions, information technologiesand digital transformation are the main factor of technological change and the condition for ensuringcompetitiveness both at the level of individual enterprises and at the level of countries and supranationalassociations, leading to the restructuring of all economic and production processes, radical improvementsin productivity, quality improvement and cost reduction goods and services. Modern world governmentalinstitutions and business environment strive for comprehensive and complex development.Thus, it becoming more evident that activities of our society require implementing new texnologies suchas digital economy. Logistics, being a complex and multistage process hugely intervening into modernmarket relationships, requires constant evolution so that it could bring more efficiency into businessand economic processes. Implementation of the digital technology into logistics may give an impulse toachieve goals set by the government. The article covers such topics, as general steps of logistics development, application of digital texnology, issuses associated with implementation of digital technologyinto logistics processes.